RESEARCH ON EMOTIONAL INTELLIGENCE AND ANXIETY IN PSYCHOLOGY STUDENTS (Psychology Travelogs, 2024)
The article is devoted to the problem of the relationship between emotional intelligence and anxiety in students of psychology and students of economics. Emotional intelligence is considered as a complex complex formation that ensures the professionalism and success of the future psychologist. The attention is drawn to the fact that the development of emotional intelligence is an important component of the professional growth of psychology students, which contributes to improving the quality of professional training and interaction with others.The results of an empirical study of the manifestation of emotional intelligence in students of psychology and students of economics are described. To study emotional intelligence, the methodology «Diagnostics of Emotional Intelligence» by N. Hall was used. The results of diagnosing situational and personal anxiety in psychology students and economics students are analysed. The Spielberger-Hanin «Anxiety Self-Assessment Scale» was used to study anxiety states. It was found that half of the psychology students experience a high level of anxiety, which is explained by the experience of military operations in Ukraine, the presence of real threats and uncertainty about the future.The peculiarities of the manifestation of emotional intelligence of psychology students and economics students with different levels of manifestation of emotional intelligence components are analysed. It is diagnosed that most future economists show low levels of development of both general emotional intelligence and its components. A comparative analysis of the level of emotional intelligence and the levels of situational and personal anxiety in psychology students and economics students is carried out.
Keywords: emotional intelligence; anxiety; situational anxiety; personal anxiety; emotional sphere; students-psychologists; students-economists